2013
DOI: 10.4028/www.scientific.net/msf.765.130
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effect of Cooling Rate on Eutectic Modification in A356 Aluminium Alloys

Abstract: In this present work, an assessment of eutectic modification based on thermal analysis was performed on modified A356 alloy. The effect of various cooling rates which were achieved by means of casting samples with various moduli in sand and metallic moulds was investigated. Cooling curves recorded from thermocouples inserted in the centre of the samples showed characteristic undercooling and recalescence associated with (Al)-Si eutectic modification. The results showed that cooling rate has a role in observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…As mentioned previously, Nogita et al [18] reported that all rare earth elements had some effect on the eutectic silicon; however, europium was the only element to cause fully modified, fine fibrous silicon, whereas the other elements only produced a minor refinement of the plate-like silicon morphology. Ferdian et al [15]. studied the effect of cooling rate on the eutectic modification in 356 alloy.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned previously, Nogita et al [18] reported that all rare earth elements had some effect on the eutectic silicon; however, europium was the only element to cause fully modified, fine fibrous silicon, whereas the other elements only produced a minor refinement of the plate-like silicon morphology. Ferdian et al [15]. studied the effect of cooling rate on the eutectic modification in 356 alloy.…”
Section: Resultsmentioning
confidence: 99%
“…Ferdian et al [16] studied the effect of cooling rate on the eutectic modification in A356 alloy. Figure 2 shows the parameters taken from thermal analysis cooling curves for characterizing the (Al)-Si eutectic arrest which, according to the authors, comprises the minimum eutectic temperature ( ,min ), maximum eutectic temperature ( ,max ), and recalescence (Δ ).…”
Section: Resultsmentioning
confidence: 99%
“…All characteristic temperatures were found to decrease continuously with increasing Sr content and solidification rate [10]. Ferdian et al [25] studied the effect of various cooling rates on eutectic modification in Sr-modified A356 alloy, using sand and metallic molds. An assessment of eutectic modification was made based on data obtained from cooling curves recorded from thermocouples inserted in the centre of the samples to determine the parameters associated with Al-Si eutectic reaction in each case.…”
Section: Resultsmentioning
confidence: 99%